A highly divergent hepacivirus-like flavivirus in domestic ducks. (8th July 2019) - Chu, Lili; Jin, Meiling; Feng, Chonglun; Wang, Xiaoyan; Zhang, Dabing
Abstract : Using random amplification and reverse transcription-PCR, a novel RNA virus was detected in sera of domestic ducks. The full genome of the virus was determined for three strains, identifying the first hepacivirus-like flavivirus in birds. The virus, that we tentatively named duck hepacivirus-like virus (DuHV), possesses several unique molecular features, such as possession of the largest hepacivirus-like polyprotein gene and a Pegivirus A -like internal ribosome entry site. Sequence comparisons and phylogenetic and sliding-window analyses indicated that DuHV is most closely related to, but highly divergent from, the known hepaciviruses. DuHV was detected in 69.7 % of 185 serum samples from four duck species and in 31 of 33 flocks from five provinces of China, reflecting a high prevalence in duck populations and a wide geographical distribution. The detection of DuHV in the same flock in November 2018 and April 2019 suggested that persistent infection can be established in the infected ducks.